2009
DOI: 10.1248/bpb.32.982
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Role of Testosterone in Organic Cation Transport: in Vivo and in Vitro Studies

Abstract: Renal organic cation transporters (OCTs) play a significant role in the elimination of a wide variety of organic cations, including endogenous compounds (e.g., monoamine neurotransmitter 1) and creatinine 2) ), drugs (e.g., cimetidine 3) metformin, 4) pramipexol 5) and cisplatin 6) ) and xenobiotics (e.g., tetraethylammonium (TEA) and 1-methyl-4-phenylpyridinium (MPP ϩ ) 3) ). OCTs are expressed in the basolateral membrane of renal proximal tubular cells, where they mediate the initial step of renal secretion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 48 publications
0
13
0
1
Order By: Relevance
“…22) In brief, after anesthesia and surgical procedures, mice were given a priming dose of 4 mCi of [ 14 C]-TEA at an infusion rate of 0.45 ml/h. Following an equilibration period of 60 min to allow plasma TEA to achieve a steady state, urine and blood samples were collected for 3 periods of 20 min each.…”
Section: Role Of Estrogen In Renal Handling Of Organic Cation Tetraementioning
confidence: 99%
See 3 more Smart Citations
“…22) In brief, after anesthesia and surgical procedures, mice were given a priming dose of 4 mCi of [ 14 C]-TEA at an infusion rate of 0.45 ml/h. Following an equilibration period of 60 min to allow plasma TEA to achieve a steady state, urine and blood samples were collected for 3 periods of 20 min each.…”
Section: Role Of Estrogen In Renal Handling Of Organic Cation Tetraementioning
confidence: 99%
“…The kidneys were removed and dissected for renal proximal tubules as described previously. 22) All dissections were performed at 4°C. Dissected tubules are collapsed and thus are only capable of basolateral transport.…”
Section: Role Of Estrogen In Renal Handling Of Organic Cation Tetraementioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that elevated Oct2 levels enhance renal clearance of the nephrotoxicant cisplatin in male rodents (142). Gonadectomy of male rats and mice decreases Oct2 mRNA as well as renal clearance of the organic cation TEA (22,143). With testosterone treatment, renal Oct2 mRNA and protein expression and TEA uptake increase to control male levels while estrogen supplementation has no effect (22,143,144).…”
Section: Expression and Regulation Of Drug Transportersmentioning
confidence: 99%